Energy efficient direction of organizational and technological design in increasing the reliability of buildings - POLTAVETS, Maryna; HALUSHKO, Dmytro (Ways to Improve Construction Efficiency, 2025)
The article presents an improved general methodology of organizational and technological design aimed at increasing the energy reliability of the process of erecting residential buildings. The expediency of taking into account energy factors at the early stages of organizational planning, which allows to ensure not only high efficiency of construction, but also to increase the energy efficiency of the future facility, has been substantiated. Particular attention is paid to the methodology for forecasting the timing of the construction of residential buildings using the probabilistic-statistical approach, which allows reducing the level of uncertainty in planning the terms and increasing the accuracy of work schedules. The influence of the intensity of work in the calendar planning on the overall reliability of construction and installation processes has been studied, the limit values of permissible deviations in the rhythm of work performance, which ensure the stability of the schedule, have been determined. Practical recommendations for optimizing organizational and technological design have been developed aimed at reducing the degree of risk of the contractor, in particular in conditions of limited resources, seasonal fluctuations and tight deadlines. Methods for improving energy efficiency at different stages of building construction – from design to commissioning – are considered separately. The conceptual foundations of the introduction of energy-efficient technologies in the practice of modern construction are theoretically substantiated. It has been proved that the combination of energy efficiency principles with modern methods of organizational and technological design helps to increase reliability, reduce energy consumption, optimize construction process management and reduce technical and organizational risks in the implementation of residential projects.